KEBIJAKAN INDONESIA MEMBUKA HUBUNGAN DIPLOMATIK DENGAN NEGARA-NEGARA KAWASAN PASIFIK ( TUVALU, NAURU, KIRIBATI) - Arif satriawan; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this research is to understand why Indonesia Foreign Policy Open The Diplomatic Relations With Pacific Region Countries (Tuvalu, Nauru, Kiribati). Indonesian relations with countries in the world has existed since Indonesi has not been established. Ranging from bilateral relations to multirateral Indonesia also complement current international relations. Foreign policy based on national interests. Indonesia have the goals and interests to cooperate with the countries of the Pacific region. Thus researcher question is why Indonesia Foreign Policy Open The Diplomatic Relations With Pacific Region Countries (Tuvalu, Nauru, Kiribati).This research theoretically has built with realism perspectives on International Relations and supported by Foreign Policy theory K.J. Holsty. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that Indonesia opened diplomatic relations with countries in the Pacific region based on national interests of Indonesia is to realize Indonesia who want to become a maritime country. Indonesia is the largest archipelago in the world with abundant marine wealth.Keywords : Foreign Policy, Indonesia, Pacific Region, Maritime country